Management of Venous Thromboembolism in Children: Current Recommendations and Therapeutic Options - Bosch A; Albisetti M (Dove Medical Press, 2020)
Alessandra Bosch, Manuela Albisetti Division of Hematology, University Children’s Hospital, Zurich, SwitzerlandCorrespondence: Manuela AlbisettiDivision of Hematology, University Children’s Hospital, Steinwiesstrasse 75, Zurich CH-8032, SwitzerlandTel +41 44 266 7138Fax +41 44 266 7171Email Manuela.albisetti@kispi.uzh.chAbstract: Venous thromboembolism has an increasing significance in the pediatric patient population. Due to the lack of well-designed pediatric clinical trials, recommendations for the treatment of venous thromboembolic events in children have low evidence and are mainly extrapolated from adult guidelines. This review summarizes and compares recommendations for the treatment of several venous thromboembolic events in children from CHEST, ASH, and the UK guidelines.Keywords: thromboembolism, thrombosis, children, treatment, guidelines